Imperata vegetation succession and carbon stocks on degraded land of beach forest in Marsegu Island, Maluku, Indonesia - Irwanto, Irwanto; Paembonan, Samuel Arung; Ngakan, Putu Oka; Maulany, Risma Illa; Sahupala, Andjela; Yatim, Hertasning (Journal of Degraded and Mining Lands Management, 2024)
Many sandy beach forests on small islands were cut down by people for farming to provide for their food needs. Land degraded due to over-exploitation is overgrown by Imperata cylindrica, which often causes fires in the dry season. This study aims to determine the species that occur in the secondary succession of Imperata grassland vegetation to assess soil fertility and differences in carbon stocks in various types of vegetation cover on the beach of Marsegu raised coral island. The measurement and calculation of carbon stocks used the Indonesian National Standard 7724:2011 with slight modifications in certain parts. The non-destructive method for calculating the above-ground and below-ground biomass used an allometric and the destructive method was carried out for understory and litter while the carbon content of the soil was taken compositely from several plots and layers and then analyzed in the laboratory. The results showed that the species that can grow and coexist with Imperata cylindrica is Timonius timon. In the final stage of the loss of Imperata cylindrica, the beach forest area was dominated by Terminalia catappa, Sterculia ceramica, and Cassia fistula. The soil's nutrient content of total N, P2O5 (available P) and cation exchange capacity (CEC) is low, with a very high sand texture percentage of 91-93%, which affects soil fertility. A comparison of total carbon stocks between differences in vegetation cover is the Imperata grassland area of 129.955 t/ha, the rehabilitation area is 82.920 t/ha, and the Terminalia vegetation is area 137.977 t/ha.